COMPARISON OF MCDM METHOD FOR SELECT ORPHANAGE - Dwi Marisa Midyanti; Rahmi Hidayati; Syamsul Bahri (LPPM Nusa Mandiri, 2020)
Multiple Criteria Decision Making (MCDM) is a decision-making method that has various techniques for solving the problem of determining the best alternative. In this study, three methods will be compared, namely CoCoSo, ARAS, and VIKOR, for the selection of Orphanages, which are the priority recipients of APBD funds. Determination of orphanage recipients from APBD funds in the Pontianak City Social Service still does manually, by only comparing the facilities and conditions of the orphanage. The CoCoSo, ARAS, and VIKOR methods can provide recommendations in the form of the rating of orphanages that can be used as a reference to determine the priorities of APBD fund recipients. The ranking produced by each method will be compared and seen the correlation coefficient value using the Spearman rank correlation. The results of this study are the three methods provide different rankings, the Spearman correlation coefficient values are very weak and weak, and there is no significant relationship between one method with other methods.